Modeling Approach for Predicting the Rate of Frequency Change of Notched Beam Exposed to Gaussian Random Excitation - Ed Habtour; Mark Paulus; Abhijit Dasgupta (Shock and Vibration)
During fatigue damage accumulation, cracks propagate through the material leading to catastrophic failure. As the cracks propagate, the natural frequency lowers, leading to a changing stress state. A new method has been developed where the damage accumulation rate is computed in the frequency domain using Linear Elastic Fracture Mechanics (LEFM), stress intensity, and the natural frequency. A finite element model was developed to predict the stress intensity and natural frequency during damage accumulation. Validation of the LEFM technique was done through comparison to experimental data. Reasonably good correlations between the FEM and the analytic model were achieved for the stress intensity and natural frequency.